Estudo da propagação de trinca por fadiga sob carregamento de amplitude variável - Cristino, Luiz Fernando [UNESP] (2011)
For engineering projects that require high reliability levels, is often not enough know only physical and chemical material properties. It’s necessary understand the failure mode of these materials in operation to ensure security level in the project and establish more stringent criteria in the analysis of structural integrity. Due to this need, aircraft industry has been using aluminum alloys in their designs and projects. “Currently more than 70% of aircraft structures are built of high strength aluminum alloys among which stand out 7075-T6 and 2024-T3 alloys, which are considered basics for being used in the new alloys development.” (PASTOUKHOV & VOORWALD, 1995). Some years ago ALCOA develops Al 2524 alloy that has emerged as refinement of Al 2024 (Al, Cu. Mg) alloy, with purpose of improve fracture toughness and fatigue resistance on structural components. The present research addresses testing of fatigue crack propagation under variable amplitude loading for Al 2024 alloy, observing the interaction effects from application of overhead blocks and plastic zone at the crack tip and makes an analysis of fracture surface images